In vitro and in vivo study of anti-tuberculosis effect of extracts isolated from Ranunculi Ternati Radix - Zhang, Lin; Li, Ruyi; Li, Mengzhu; Qi, Zhongjie; Tian, Jingkui (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2015)
Aim: This study was designed to investigate the anti-tuberculosis activities of Ranunculi Ternati Radix extracts to demonstrate the effect of active part of Ranunculi Ternati Radix, which could be enriched through macroporous resin, on mycobacterium tuberculosis infections. Materials and methods: In vitro, the anti-tuberculosis activity of its water extract (WE), 70% ethanol extract (EE), water eluted part of EE from D101 macroporous resin (WEPMR), 70% ethanol eluted part of EE from D101 macroporous resin (EEPMR) was conducted using H37Rv. Then EEPMR of better anti-tuberculosis activity was chosen to carry out anti-tuberculosis activity test against MDR2314-2 and XDR1220. In vivo, the anti-tuberculosis activities of EEPMR, Ranunculi Ternati Capsules and Isoniazid alone or in combination with different doses were evaluated on mouse model infected H37Rv. Results: In vitro, EEPMR had inhibitory effect on H37Rv, MDR2314-2 and XDR1220. In vivo study, both medium and high dose of EEPMR alone had therapeutic effect on chronic tuberculosis in mouse. No acute toxicity was identified of EEPMR at a dose of 12.0 g·kg-1. Conclusions: EEPMR possessed better anti-tuberculosis effects than other extracts and Radix Ranunculi Ternati Capsules. This supported the use of macroporous resin to enrich the active part of Ranunculi Ternati Radix to cure mycobacterium tuberculosis infections.